PRINCIPIES IN CALL SOFTWARE DESIGN AND IMPLEMENTATION - Gimeno Sanz, Ana (International Journal of English Studies, 2002)
This paper discusses a number of principles to bear in mind when designing and impleinenting multimedia language learning materials. Issues such as personnel and tools are briefly looked at. The general programme design principles referred to are based on courseware features such as log-on, menus and hierarchy, reference materials, utilities, student recording devices, feedback, progress reports and exercises. A general overview is given on the template approach to designing and creating a multimedia CALL package. Throughout the paper examples are given from the author’s own experience in multimedia development for language learning purposes.